Efforts to Improve Cognitive Learning Outcomes of Grade 2 Students of Junganyar 2 State Elementary School in Mathematics Subjects Through LKPD - Rahma Dwi Novitasari (Sekolah Tinggi Agama Islam Nurul Islam Mojokerto, 2025)
This classroom action research investigated the effectiveness of Learner Worksheets (LKPDs) in improving the cognitive learning outcomes of 2nd-grade students in mathematics, specifically addition with carrying, at SD Negeri Junganyar 2. The study, conducted over two cycles, involved 34 students and utilized pre- and post-tests, observations, and student questionnaires. Results showed a significant increase in students' average scores after implementing the LKPDs, rising from 40% in the pre-test to 80.88% in the post-test of cycle 2. The LKPDs, designed collaboratively with the classroom teacher, fostered deeper conceptual understanding and increased student engagement. While positive, the study acknowledges methodological limitations and suggests further research with a more robust design.